Enhancing Furosemide Bioavailability Using Liquisolid Compacts With Mixed Solvency Approach - Krutika Magar; Pooja Dalvi; Pragati Gangan; Shreya Jadhav; Sakshi Ghadigaonkar; Jashoda Chaudhary (Asian Journal of Pharmaceutical Research and Development, 2026)
Objective(s): To study the synergy of using both the Liquisolid Technique and the Mixed Solvency Approach for improving the solubility and oral bioavailability of Furosemide, which is a BCS Class IV drug. Sources: An exhaustive review of literature from the field of pharmacy with regards to liquisolid techniques, mixed solvency approaches, and furosemide pharmacokinetics. Summary: The liquisolid technique helps enhance the dissolution rate by incorporating the active substance molecularly in a non-volatile solvent, sometimes resulting in an amorphous state with high energy levels. On the other hand, the concept of mixed solvency resolves the problem of high doses in normal liquisolid techniques by using a combination of safe solvents to increase the amount of drug in the liquid matrix. Conclusion: Integrated technology offers an efficient and flexible strategy for formulation of high dose oral formulations that dissolve faster than conventional drug forms.